The Role of Hizbullah in the Time of Indonesian Revolution in Bandung, 1945-1946 - Sulasman, Sulasman (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: Hizbullah, its meaning is the army of Allah (God), established at the time of the Japanese occupation in Indonesia (1942-1945), and has been restructured after the proclamation of independence along with the spirit of revolution in Indonesia (1945-1950). Hizbullah was founded because the Muslims young people feel to have an obligation in assisting the nation-state and religious struggle to be free from the colonialism in Indonesia. This article attempts to explain the position and role of Hizbullah organization, which was established after the proclamation of Indonesian independence by the creativity of local Muslims young people. Increased establishment of semi-military organizations, including the Hizbullah organization in Bandung, is the reaction of the arrival of the Allied Forces in Indonesia. British Allied Forces, which accompanied by the Dutch NICA (Netherland-Indies Civil Administration), their arrival was greeted by Indonesian people with a sense of suspicion and awareness of independence. One of the incidents between British Allied Forces and Dutch NICA, after arriving in Bandung, against the people of Indonesia that involves the TKR (Indonesian Peoples Security Army) and Hizbullah, is the Fokkerweg bettle in Bandung city. This battle lasted for 3 days and 3 nights. The battle was fierce, which is characterized by a combination between frontal attacks and diplomacy. This suggests that the position and the role of Hizbullah, in the context of Indonesias independence struggle, is very important and has contributed greatly to the formation of TKR, which later became the TNI (Indonesian National Army).KEY WORD: Hizbullah, revolution, Bandung city, the role and function, freedom and independence, organization and struggle, and Indonesian army.Â RESUME: âPeranan Hizbullah pada Masa Revolusi Indonesia di Bandung, 1945-1946â. Hizbullah , artinya tentara Allah, didirikan pada saat pendudukan Jepang di Indonesia (1942-1945) dan telah direstrukturisasi setelah proklamasi kemerdekaan bersama dengan semangat revolusi di Indonesia (1945-1950). Hizbullah didirikan karena orang-orang muda Islam merasa memiliki kewajiban untuk membantu perjuangan negara-bangsa dan agama agar bebas dari penjajahan di Indonesia. Artikel ini mencoba untuk menjelaskan posisi dan peran organisasi Hizbullah, yang didirikan setelah proklamasi kemerdekaan Indonesia oleh kreativitas anak-anak muda Muslim setempat. Meningkatnya pendirian organisasi semi-kemiliteran, termasuk organisasi Hizbullah di Bandung, merupakan reaksi dari kedatangan Tentara Sekutu di Indonesia. Tentara Sekutu Inggris, yang diboncengi oleh NICA (Pemerintahan Sipil Hinda-Belanda) Belanda, kedatangan mereka disambut oleh rakyat Indonesia dengan perasaan curiga dan kesadaran akan kemerdekaan. Salah satu insiden antara Tentara Sekutu Inggris dan NICA Belanda, setelah tiba di Bandung, melawan rakyat Indonesia yang melibatkan TKR (Tentara Keamanan Rakyat) dan Hizbullah adalah pertempuran Fokkerweg di Kota Bandung. Pertempuran ini berlangsung selama 3 hari dan 3 malam. Pertempuran berlangsung sengit, yang ditandai oleh kombinasi antara serangan frontal dan diplomasi. Hal ini menunjukkan bahwa kedudukan dan peran Hizbullah, dalam konteks perjuangan kemerdekaan Indonesia, adalah penting dan telah memberikan sumbangan besar bagi pembentukan TKR, yang kemudian berubah menjadi TNI (Tentara Nasional Indonesia).KATA KUNCI: Hizbullah, revolusi, kota Bandung, peran dan fungsi, kebebasan dan kemerdekaan, organisasi dan perjuangan, serta tentara Indonesia.About the Author: Dr. Sulasman is a Senior Lecturer at the Department of Islamic Civilization, Faculty of Adab and Humanity UIN (State Islamic University) Sunan Gunung Djati, Jalan Jenderal A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. Corresponding author is: sulasman14@yahoo.comHow to cite this article? Sulasman. (2014). âThe Role of Hizbullah in the Time of Indonesian Revolution in Bandung, 1945-1946â in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7, No.1 [Mei], pp.65-78. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of article: Accepted (March 11, 2014); Revised (April 17, 2014); and Published (May 20, 2014). Â Â